BENEFITS OF CHILD‐FOCUSED ANXIETY TREATMENTS FOR PARENTS AND FAMILY FUNCTIONING. Issue 9 (6th February 2013) - Keeton, Courtney P.; Ginsburg, Golda S.; Drake, Kelly L.; Sakolsky, Dara; Kendall, Philip C.; Birmaher, Boris; Albano, Anne Marie; March, John S.; Rynn, Moira; Piacentini, John; Walkup, John T.
<x xml:space="preserve">Abstract</x> Background To examine (1) changes in parent (global psychological distress, trait anxiety) and family (dysfunction, burden) functioning following 12 weeks of child‐focused anxiety treatment, and (2) whether changes in these parent and family factors were associated with child's treatment condition and response. Methods Participants were 488 youth ages 7–17 years (50% female; mean age 10.7 years) who met DSM‐IV‐TR criteria for social phobia, separation anxiety, and/or generalized anxiety disorder, and their parents. Youth were randomly assigned to 12 weeks of "Coping Cat" individual cognitive‐behavioral therapy (CBT), medication management with sertraline (SRT), their combination (COMB), or medication management with pill placebo (PBO) within the multisite Child/Adolescent Anxiety Multimodal Study (CAMS). At pre‐ and posttreatment, parents completed measures of trait anxiety, psychological distress, family functioning, and burden of child illness; children completed a measure of family functioning. Blinded independent evaluators rated child's response to treatment using the Clinical Global Impression‐Improvement Scale at posttreatment. Results Analyses of covariance revealed that parental psychological distress and trait anxiety, and parent‐reported family dysfunction improved only for parents of children who were rated as treatment responders, and these changes were unrelated to treatment condition. Family burden and child‐reported family dysfunction improved significantly from pre‐ to posttreatment regardless of treatment condition or response. Conclusions Findings suggest that child‐focused anxiety treatments, regardless of intervention condition, can result in improvements in nontargeted parent symptoms and family functioning particularly when children respond successfully to the treatment.